Muscle typology does not influence peak-intensity periods, subsequent recovery, or match-running declines toward the end of a match in professional male football - Van de Casteele, F.; Van Haaren, J.; Deprez, D.; Bellinger, P.; Minahan, C.; Lievens, E.; Derave, W. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To investigate the influence of muscle typology on match-running decrements toward the end of the match, peak-intensity periods, and the subsequent recovery in professional male football.